Solidagenone from Solidago chilensis Meyen Protects against Acute Peritonitis and Lipopolysaccharide-Induced Shock by Regulating NF-κB Signaling Pathway - Ivanilson Pimenta Santos; Laís Peres Silva; Dahara Keyse Carvalho Silva; Bruna Padilha Zurita Claro dos Reis; Temistocles Barroso de Oliveira; Andressa Maia Kelly; Edivaldo dos Santos Rodrigues; Claudia Valeria Campos de Souza; José Fernando Oliveira-Costa; Simone Sacramento Valverde; Osvaldo Andrade Santos-Filho; Milena Botelho Pereira Soares; et al. (MDPI AG, 2024)
Anti-inflammatory agents are widely used for the treatment of inflammatory diseases. Nevertheless, the associated side effects of the available drugs make it necessary to search for new anti-inflammatory drugs. Here, we investigated the anti-inflammatory activity of solidagenone. Initially, we observed that a single dose of 30, 60, or 90 mg/kg of solidagenone did not result in mortality or elicit any discernible signs of toxicity in mice. At the same doses, solidagenone promoted a significant reduction in the migration of neutrophils in an acute peritonitis model and decreased mortality in a lipopolysaccharide-induced endotoxic shock model. Interestingly, treatment with solidagenone conferred a protective effect against leukopenia and thrombocytopenia, hematological disorders commonly observed in sepsis conditions. In addition, treatment with all the doses of solidagenone promoted a significant reduction in nitric oxide, TNF-α, and IL-1β levels relative to the LPS-stimulated vehicle-treated cultures. Furthermore, gene expression and in silico analyses also supported the modulation of the NF-κB pathway by solidagenone. Finally, in silico pharmacokinetics predictions indicated a favorable drugability profile for solidagenone. Taken together, the findings of the present investigation show that solidagenone exhibits significant anti-inflammatory properties in acute experimental models, potentially through the modulation of the NF-κB signaling pathway.